HEGEMONI BUDAYA INDUSTRI DALAM PENDIDlKAN KONTEMPORER - adminBambang Syaeful Hadi; Iffah Nurhayati (LPMPP Universitas Negeri Yogyakarta, 2002)
The industrial culture as a product ofan increasingly industrial society has greatly influenced the educational system.Its hegemony in the educational system has shifted educationalidealism. Since the industrial culture assumes that man is afactor in production, the aim of education has started tochangefrom its original course for the sake of meeting thedemandsof the industrial field, the market for its product. Afurther consequence of this is that the output of educationno longer meets the expectation concerning what is essentiallyworthy to be the objectiveof education, which is to develophuman resources with all their potentials into better individualswho are independent and increasingly awareof the essence oftheir humanity.There are supposed to be three main agents of education,i.e., the family, the school, and society. However, today the schooltends to be the main support ofeducation while the educatiomil .system runningat schools now in operation has diverged fromthe original idealismofeducation. Education in one alternative.religion, Islam, has not achieved what is intended by the Koranand Hadits, either, because there are not yet any adequate willand ability among Moslems to interpret creatively the religiousteachings and transfer them into some formof educational system together with its operational steps.The hegemonyofindustrial culture has